2019
DOI: 10.1177/0031512519848221
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Neuroticism and Executive Function Outcomes: Response Inhibition and Sustained Attention on a Continuous Performance Test

Abstract: There are known relationships between psychopathology, personality, and executive function (EF), though the association between personality and EF, independent of psychopathology, remains understudied. The present study investigated relationships between Five Factor Model personality traits and indices of response inhibition, sustained attention, and response variability on a continuous performance test (CPT) among 50 healthy adults (male = 27, female = 23; Mage = 19.9 years, range 18–24 years) of primarily Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…The first aim of this study was to determine the existence of a link between neuroticism and EF in older adults. Although certain of the previous studies reported negative cross-sectional links between neuroticism and EF in younger adults (Crow, 2019;Murdock et al, 2013;Purić and Pavlović, 2012;Schretlen et al, 2010), other cross-sectional studies reported inconsistent results in older adults (Bell et al, 2020;Booth et al, 2006;Boyle et al, 2010;Chapman et al, 2017;Denburg et al, 2009;Hill et al, 2015;Kim et al, 2021;Turunen et al, 2020;Williams et al, 2010). Importantly, the only longitudinal study so far did not find a longitudinal link between neuroticism and EF among older adults when assessed across a relatively short period of time (i.e., two years, Waggel et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The first aim of this study was to determine the existence of a link between neuroticism and EF in older adults. Although certain of the previous studies reported negative cross-sectional links between neuroticism and EF in younger adults (Crow, 2019;Murdock et al, 2013;Purić and Pavlović, 2012;Schretlen et al, 2010), other cross-sectional studies reported inconsistent results in older adults (Bell et al, 2020;Booth et al, 2006;Boyle et al, 2010;Chapman et al, 2017;Denburg et al, 2009;Hill et al, 2015;Kim et al, 2021;Turunen et al, 2020;Williams et al, 2010). Importantly, the only longitudinal study so far did not find a longitudinal link between neuroticism and EF among older adults when assessed across a relatively short period of time (i.e., two years, Waggel et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…According to the Big Five Model, neuroticism is characterized by irrationality of thoughts, low ability to manage impulsions and stress, emotional instability, and consequently, a higher risk of developing psychiatric disorders (Costa and McCrae, 1992). However, while the negative relationship between neuroticism and EF seems well established in younger adults (Crow, 2019;Murdock et al, 2013;Purić and Pavlović, 2012;Schretlen et al, 2010), research on older adults is still inconsistent. Indeed, certain studies did not find a significant link between neuroticism and EF (Boyle et al, 2010;Hill et al, 2015;Turunen et al, 2020;Waggel et al, 2015), whereas others found that neuroticism was negatively associated with EF in older adults (Bell et al, 2020;Booth et al, 2006;Chapman et al, 2017;Denburg et al, 2009;Kim et al, 2021;Williams et al, 2010).…”
mentioning
confidence: 99%
“…A higher frequency of multiple responses in action also appears. A high level of neuroticism seems to be associated with making mistakes [24]. However, there seems to be much more behind the relationship between neuroticism and cognitive performance.…”
Section: Discussionmentioning
confidence: 95%
“…Cognitive and executive functions appear to be associated with some personality traits. Nevertheless, the association between personality and cognitive and executive functions remains understudied [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the positive relation between reward and habitualness decreased as neuroticism increased (Figure 15). One speculative possibility is that the strong emotional reactions associated with neuroticism deplete the regulatory resources available for monitoring reward and adapting behavior as reward changes (124). As a consequence, behavior becomes increasingly ballistic as poorly monitored behaviors become rigidly automated in response to situational cues.…”
Section: The Relation Of Reward To Habitualnessmentioning
confidence: 99%